2016
DOI: 10.1038/srep38529
|View full text |Cite|
|
Sign up to set email alerts
|

Arctic megaslide at presumed rest

Abstract: Slope failure like in the Hinlopen/Yermak Megaslide is one of the major geohazards in a changing Arctic environment. We analysed hydroacoustic and 2D high-resolution seismic data from the apparently intact continental slope immediately north of the Hinlopen/Yermak Megaslide for signs of past and future instabilities. Our new bathymetry and seismic data show clear evidence for incipient slope instability. Minor slide deposits and an internally-deformed sedimentary layer near the base of the gas hydrate stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 43 publications
3
32
1
1
Order By: Relevance
“…Some parts of the canyons are relatively smooth, which may indicate the deposition by contour currents. In the eastern part of the Hinlopen scar, Geissler et al () also suggested sediment wave development. This suggestion fits well with results from this study that indicate a western increase in the influence of contour currents (Figure b).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Some parts of the canyons are relatively smooth, which may indicate the deposition by contour currents. In the eastern part of the Hinlopen scar, Geissler et al () also suggested sediment wave development. This suggestion fits well with results from this study that indicate a western increase in the influence of contour currents (Figure b).…”
Section: Discussionmentioning
confidence: 96%
“…The overall quality of the bathymetric and seismic data is good. The seismic interval velocity for depth conversion was derived from Geissler and Jokat (2004). The velocity range is 2.1-2.7 km/s for the deeper strata (NB-2; Figure 4), resulting in an average velocity of 2.3 km/s (Geissler & Jokat, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations